2018
DOI: 10.5194/amt-2018-166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The CALIPSO Version 4 Automated Aerosol Classification and Lidar Ratio Selection Algorithm

Abstract: Abstract. The Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) version 4.10 (V4) level 2 aerosol data products, released in November 2016, include substantial improvements to the aerosol subtyping and lidar ratio selection algorithms. These improvements are described along with resulting changes in aerosol optical depth (AOD). The most fundamental change in V4 level 2 aerosol products is a new algorithm to identify aerosol subtypes in the stratosphere. Four aerosol subtypes are introduced for the stra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(134 citation statements)
references
References 71 publications
1
133
0
Order By: Relevance
“…Obviously particle shape and size widely control the strength of depolarization of backscattered laser radiation at the different wavelengths. However, to obtain clear answers concerning the role of particle size, shape, and composition on light depolarization, we need extended simulation studies with advanced optical particle models (Gasteiger et al, 2011;Lindqvist et al, 2014;Kemppinen et al, 2015a, b;Mishchenko et al, 2016). Unfortunately, modeling of the optical properties of dust and soot particles for our specific lidar application (scattering at exactly 180 • ) is a very crucial task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously particle shape and size widely control the strength of depolarization of backscattered laser radiation at the different wavelengths. However, to obtain clear answers concerning the role of particle size, shape, and composition on light depolarization, we need extended simulation studies with advanced optical particle models (Gasteiger et al, 2011;Lindqvist et al, 2014;Kemppinen et al, 2015a, b;Mishchenko et al, 2016). Unfortunately, modeling of the optical properties of dust and soot particles for our specific lidar application (scattering at exactly 180 • ) is a very crucial task.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental input parameters in the CALIOP data analysis are the particle extinction-to-backscatter ratio (lidar ratio) at 532 and 1064 nm (Omar et al, 2009;Kim et al, 2018). Observations of the lidar ratio at these two wavelengths for all important aerosol types (e.g., urban haze, marine aerosol, biomass-burning smoke, desert dust) and frequently occurring mixtures of smoke pollution with mineral dust or marine particles with urban haze are a prerequisite to permit accurate aerosol profiling with CALIOP on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Version 4 level 2 benefits from a number of major improvements relevant to the level 3 aerosol product. Most significantly, updated aerosol lidar ratios and aerosol subtyping corrections (Kim et al, 2018) will have the largest impact on σ and AOD reported by level 3 since these quantities are non-linear functions of lidar ratio (nearly linear at low optical depths). The overall structure of the level 3 aerosol profile product will 5 remain similar in terms of grid size and science data sets, but the quality filtering strategy described in this paper may change to account for modifications in version 4 level 2 processing.…”
Section: Discussionmentioning
confidence: 99%
“…The CALIOP L3 aerosol profile monthly product creation is described by Tackett et al () and is provided at 2° latitudinal by 5° longitudinal resolution. The current standard L3 products use version 3 L2 inputs; version 4 L2 products have been developed (Kim et al, ; Young et al, ), based on improved calibration (Getzewich et al, ; Kar et al, ) and addressing algorithmic issues which (in part) contributed to a low bias in version 3 data. However, version 4 inputs have not yet been incorporated into the standard L3 products.…”
Section: Comparison To Other Over‐water Satellite Data Setsmentioning
confidence: 99%